Wideband linearisation technique for radio over fiber laser transmitter - Alifah, Suryani (Institute of Electrical and Electronics Engineers, 2009)
This paper presented the predicted performance of the low cost optical transmitter employing feedforward linearisation technique. The design are able to give significant reduction of third order IMD products up to 30 dB for system operating at 5 - 5.8 GHz band.